Modelling the power demand during the 200 m flying start cycling event: application to a world-class track cyclist - Dorel, S.; Hautier, C.; Rambaud, O.; Rouffet, D.; Lacour, J. R.; Bourdin, M. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
The aim of this study was, therefore, to apply an adapted mathematical model to sprint track cycling in order to assess the contribution of each component in power demand during the 200 m event.